Biological markers of Alzheimer's disease in cerebrospinal fluid: clinical and laboratory comparisons - K. V. Shevtsova; D. O. Rozhkov; D. A. Grishina; V. V. Grinyuk; V. V. Zakharov; N. M. Kashakanova; N. N. Koberskaya; O. V. Kosivtsova; A. B. Lokshina; Yu. A. Starchina; A. Yu. Tyurina; A. Yu. Fedorova; et al. (Неврология, нейропсихиатрия, психосоматика)
Diagnostic hypothesis of Alzheimer's disease (AD) is based on the typical clinical picture of the disease and the exclusion of other diseases manifesting by cognitive and behavioural disorders by MRI scans of the brain and laboratory tests. For an accurate diagnosis of AD and exclusion of other diseases, detection of biological markers (biomarkers) of AD in the cerebrospinal fluid (CSF) is of great importance: a decrease in the level of beta-amyloid (Ав^ -42) and an increase in the level of phosphorylated tau protein. The analysis of AD biomarkers in the CSF of 63 patients (16 men and 47 women, mean age 72±8.7 years) with a typical picture of AD [30 patients in the moderate cognitive impairment (MCI) stage and 33 in the mild dementia stage] allowed us to confirm the diagnosis in 54 cases (85.3%) and to exclude it in the remaining nine patients (14.7%). We present a case of a 59-year-old patient with MCI in whom biomarkers typical of AD were detected in the CSF, confirming the diagnosis of AD. We also present the observations of two patients with possible AD, in whom the results of the CSF examination made it possible to rule out AD and indicated hippocampal sclerosis and tauopathy. At present, an accurate diagnosis of AD based on the study of biomarkers of the disease is of great practical importance, since at the stage of MCI and mild dementia it is possible to prevent the progression of AD with anti-amyloid therapy. Currently, AD is rarely diagnosed in our country, so it is of great importance to inform physicians about modern methods of diagnosis and treatment of AD.